Risk assessment of an interacting structure soil system due to liquefaction. - Koutsourelakis, Steve
The present study deals with the non-linear stochastic dynamic analysis of a soil structure interacting system. The ultimate objective is to determine the risk of damage to the system due to liquefaction under a wide range of earthquake intensities. A Monte Carlo simulation approach is followed in conjunction with advanced finite element procedures. The stochastic spatial variability of soil properties and the randomness of the seismic excitation are taken into account in order to estimate the statistics of the response, measured in terms of uniform foundation settlement and tilting. Specifically, soil properties are modelled as non-Gaussian random fields and seismic excitations as non-stationary random processes. The probabilistic characteristics of the stochastic field modelling soil properties are established from in situ tests. The risk of damage to the soil structure system due to liquefaction is assessed by establishing fragility curves, which are of paramount importance of risk assessment and management studies of such systems. Fragility curves express the probability of exceeding various thresholds in the response. The relative effect of the variability of various soil parameters on the variability of the response is also examined.
Keywords: Stochastic material properties; Liquefaction; Fragility curves; Geotechnical engineering